Assessing gender differences in the relationship between religious coping responses and alcohol consumption. Issue 1 (2nd January 2018) - Krause, Neal; Pargament, Kenneth I.; Hill, Peter C.; Ironson, Gail
ABSTRACT: The purpose of this study is to see if the use of religious coping responses is associated with alcohol intake. In addition, tests are conducted to see if the relationship between religion and alcohol use varies by gender. Data from a recent nationwide survey ( N  = 2173) indicate that greater use of religious coping responses is associated with less alcohol consumption. The findings further reveal that even though women use religious coping responses more often than men, the relationship between the use of religious coping responses and alcohol consumption is stronger for men than for women. This suggests that, with respect to alcohol consumption, men may benefit more from using religious coping responses than women. The theoretical implications of these results are discussed.